Molecular analysis of cryptosporidiosis on cattle farms in Gran Canaria, Canary Islands (Spain) - María Cristina Del Río; Sergio Martín; Joaquín Quílez; Claudia Vergara-Castiblanco; José Manuel Molina; Otilia Ferrer; Magnolia María Conde; José Adrián Molina; Antonio Ruiz (International Journal of Veterinary Science and Medicine)
Cryptosporidium spp. infections in calves cause serious economic losses in livestock and pose an important zoonotic risk. The aim of this study was to investigate the prevalence of Cryptosporidium spp. in cattle on the island of Gran Canaria. Faecal samples were collected from calves and adult cattle from a total of 15 farms, and a questionnaire survey was conducted to farmers. The presence of Cryptosporidium spp. oocysts in faeces was determined by microscopy, showing infection rates of 45.9% in calves and 4.1% in adults, with positive correlation with the faecal scores of infected animals (p < 0.0001). Samples were amplified by PCR targeting SSU rRNA, with positivity rates for calves and adults being 51.7% and 31.7%, respectively. The PCR-positive samples were further genotyped and sequenced for the 60 kDa glycoprotein gene (GP60) and the microsatellite TP14. Four Cryptosporidium species were identified (C. parvum, C. ryanae, C. bovis, and C. andersoni), of which C. parvum was the most frequent in calves (45.8%) and adults (29.2%). GP60 sequencing revealed that all C. parvum samples belonged to the IId family, the most frequent subtypes being IIdA22G1 and IIdA23G1. Overall, the results of this study demonstrate a high occurrence of Cryptosporidium spp. in both calves and adult cattle, including the zoonotic IId family of C. parvum. These findings have significant implications for cattle farming and public health. The lack of awareness among farmers regarding cryptosporidiosis highlights the need for caution to prevent epidemiological outbreaks that could impact both human and livestock health.